(untitled) (Journal of Digital Learning Futures p-ISSN 3117-6054 and e-ISSN 3117-6062, 2025)
Gamification—the integration of game-based techniques such as points, badges, leaderboards, quests, and rewards into learning environments—has become a transformative strategy in digital education. This research investigates the impact of gamified learning platforms on student motivation, creativity, and skill development. Using a mixed-method research design, data were collected from 420 students across three online learning platforms (Coursera, Duolingo, and Khan Academy). Results demonstrate that gamification increases student motivation by 37%, creativity indicators by 28%, and skill acquisition by 32%. Gamified elements such as immediate feedback, progressive challenges, and social competition foster deeper engagement, intrinsic motivation, and persistence in learning. The study concludes that gamification significantly enhances learning effectiveness and should be integrated strategically into online course design.